How cities reshape food systems - Minten, Bart (2017)
Bart Minten “Food Security and Nutrition in an Urbanizing World” June 06, 2017 Brussels, Belgium The International Food Policy Research Institute (IFPRI), SNV Netherlands Development Organization, and Welthungerhilfe are jointly organizing a one-day event in Brussels on the eve of the European Development Days to explore the challenges and opportunities of urbanization from a variety of perspectives.